Effect of improved parboiling methods on the physical and cooked grain characteristics of rice varieties in Benin - Fofana, M.; Wanvoeke, J.; Manful, J.T.; Futakuchi, K.; Mele, P. van; Zossou, E. (2011)
The efficiency of traditional, intermediate and improved parboilers was compared through theireffects on certain physical and cooking quality traits. Two varieties (NERICA 4 and Gambiaka) commonlycultivated and consumed in Benin were used. Results showed that the traditional parboiler had the highestlevel of heat-damaged grains (90%) with the improved equipment having the least (17%). The improved andintermediate parboiling technology produced grains of comparable hardness (4 kg and 6 kg, respectively, forGambiaka and NERICA 4) while the traditional method resulted in a sample with the least hardness for bothGambiaka (4 kg) and NERICA 4 (3 kg). The improved method and the intermediate technology using woodensticks at the bottom of the vessel had higher water uptake (2.97 ml/grain) and grain swelling ratios (5.41) ascompared to the traditional and intermediate methods using a container with a perforated bottom.